Storytelling as an Active Learning Tool to Engage Students in a Genetics Classroom - Karobi Moitra (American Society for Microbiology, 2014)
Storytelling is an ancient art that originated long before the written word. Storytelling interspersed with traditional lectures has been used as a teaching tool in an Introductory Genetics course. Students have eagerly responded to the storytelling pedagogy, suggesting that it can be leveraged to help students grasp complicated theories, engage students, and help improve student retention in STEM fields.